Pedagogy and social class in a brazilian urban setting - Silva, Tomaz Tadeu da (1984)
Education systems contain differentiating internal processes that treat students differently according to their social class origins. A growing body of literature, inspired by Bowles and Gintis (1976) among others, has noted that this differentiating process is linked to a larger process of social reproduction perpetuating the existing social and economic structure. The present study was designed to further elucidate the ways in which the distribution of educational resources contributes to a process of social and cultural reproduction. Three schools in the southern Brazilian city of Porto Alegre were studied for this purpose: a private instutition serving an upper class clientele; a public school serving children of the middle class; and a public school attended by working-class children. Two classrooms at each of the three schools were intensively observed during the first semester of 1983. Teachers and staff were interviewed concerning their pedagogical views. Patterns of instruction and control observed at the three schools suggest that children from different social classes receive substantially different kinds of schooling. Upper class children experience teaching emphasizing processes of conceptualization and method rather than memorization of isolated bits of information. Oral and other forms of self-expression are given ample emphasis in resolving open-ended instructional tasks. Negotiation and discursive reasoning usually substitute imperative modes of control. In contrast, schoolwork at the working-class school is characterized by limited oral interaction. Classroom activities emphasize copy, drills and textbook exercises. Imperative commands are the preferred forms of control. Instructional methods used at the middle-class public school also emphasize textbook learning and drills, but with an unusual degree of urgency and diligence that was absent at the working-class school. Direct commands and exhortations are used to maintain discipline. The most obvious distinction in ideological discourse observed among staff members at the three schools concerns the existence of na explicit pedagogy endorsed at the private school and the concomitant absence of any such similar rationale at the other two schools. Whereas the private school staff endorses an explicit set of educacional concepts, values, and principles, which tive coherence and purpose to their activities, staff members at the other two schools are guided by commonsensical views of the objctives of schooling provided. This commonsensical understanding shares implicit assumptions about the kind of schooling that will best serve the children of a specific social class.